A novel SBF1 missense mutation causes autosomal dominant Charcot–Marie–Tooth disease type 4B3 - Liu, Huaqi; Dong, Jing; Xie, Zhe; Yu, Li (Frontiers in Neurology, 2024)
IntroductionWe present a case of autosomal dominant Charcot–Marie–Tooth disease type 4B3 (CMT4B3) in a family caused by a novel SBF1 missense mutation.MethodsTwo patients, a mother and daughter, were recruited from our hospital. Both exhibited early-onset symptoms, including distal muscle atrophy of the limbs, without cranial nerve involvement. Electromyography was performed to assess nerve amplitudes and conduction velocities. Whole-exome sequencing (WES) and Sanger sequencing were performed to identify genetic mutations.ResultsElectromyography revealed a significant decline in nerve amplitudes, while the nerve conduction velocities (NCVs) remained normal in the extremities. Sequencing identified a novel missense mutation (c.1398C > A, p.H466Q) in exon 13 of the SET binding factor 1 (SBF1) gene in both patients, indicating an autosomal dominant inheritance pattern.DiscussionPathogenicity and protein predictions suggest that the myotubularin-related protein 5 (MTMR5), encoded by the mutated SBF1, may possess an altered structure, resulting in disease. These findings will help expand the phenotypic and genetic spectrum of CMT4B3.